THE SNOWMAN - Nesbo, Jo (Kino Lorber, 2026)
From executive producer Martin Scorsese, The Snowman is based on Jo Nesb₂̜s New York Times bestselling thriller series. When an elite Norwegian crime squad₂s lead detective investigates the disappearance of a victim on winter₂s first snow, he fears an elusive serial killer may be active again. With the help of a brilliant recruit, the cop must connect decades-old cold cases to the brutal new one if he hopes to outwit the killer before the next snowfall.